Association of Mediterranean, high-quality, and anti-inflammatory diet with dementia in UK Biobank cohort - Ji-eun Youn; Yu-Jin Kwon; Yae-Ji Lee; Seok-Jae Heo; Ji-Won Lee (The Journal of Nutrition, Health and Aging)
Background: This study examined the relationship between adherence to the Mediterranean diet, MIND diet, Recommended Food Score (RFS), Alternative Healthy Eating Index (AHEI), and Energy-adjusted Dietary Inflammatory Index (EDII) and dementia risk in a large UK population cohort. Methods: We analyzed data from 131,209 participants in the UK Biobank, aged 40–69 years, with no prior diagnosis of dementia at baseline. Dietary intake was assessed using the validated Oxford WebQ tool, and adherence to each dietary pattern was calculated. Dementia incidence was identified using algorithmically defined outcomes based on ICD codes. Fine–Gray subdistribution hazard models adjusted for sociodemographic, genetic, and lifestyle factors were applied to examine the association between dietary indices and dementia risk. Subgroup analyses were conducted based on age, sex, obesity status, and ApoEε4 status. Results: Over a median follow-up of 13.5 years, 1453 dementia cases were identified. Higher adherence to the MEDAS, MIND diet, RFS, and AHEI was significantly associated with reduced dementia risk (HRs: 0.79, 0.73, 0.72, and 0.77, respectively). Conversely, higher EDII scores, indicating pro-inflammatory diets, were linked to an increased dementia risk (HR: 1.3). These associations were more pronounced in older adults (≥60 years), women, non-obese individuals, and ApoEε4 non-carriers. Subgroup analyses revealed differential impacts of dietary patterns based on demographic and health-related factors. Conclusion: Greater adherence to Mediterranean, MIND, and high-quality diets is associated with a lower risk of dementia, while pro-inflammatory diets increase the risk. High-quality anti-inflammatory diets play a significant role in reducing the risk of dementia, with stronger effects observed in specific subgroups.